Examination of the Extreme Response Style of Students using IRTree: The Case of TIMSS 2015 - Münevver İlgün Dibek (International Journal of Assessment Tools in Education)
Inthe literature, response style is one of the factors causing anachievement-attitude paradox and threatens the validity of the results obtainedfrom studies. In this regard, the aim of this study is two-fold. Firstly, itattempts to determine which item response tree (IRTree) models based on thegeneralized linear mixed model (GLMM) approach (random intercept, randomintercept with the fixed effect of extreme response and random intercept-slopemodel) best fit the Trendsin International Mathematics and ScienceStudy(TIMSS) 2015 data. Secondly, it purports to explore how the extremeresponse style affects students’ attitudes toward mathematics of students. Thisstudy is both basic research and descriptive research in terms of seeking foranswers for two different research questions. For the sample of this research,15 countries were randomly selected among countries participated in TIMSS 2015.The students’ responses to items measuring attitude in the studentquestionnaire were analyzed with the packages “lme4” and “irtrees” in Rsoftware. When the model fit indices were evaluated, the random intercept-slopemodel was found to be the best fit to the data. According to this model, theextreme response style explains a significant amount of variances in the students’attitude toward mathematics. Additionally, students with a negative attitudetoward mathematics were found to have an extreme response style. It wasconcluded that an extreme response style had an effect on students’ attitude.